STUDI PERSEPSI MASYARAKAT TERHADAP MANFAAT BANTUAN LANGSUNG TUNAI DI DESA ALO’O DAN DESA OGOLUGUS KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG (STUDI KASUS DESA PEGUNUNGAN DAN DESA PESISIR) - Sudirman, Sudirman (Katalogis, 2014)
This study analyze perceptions of beneficiaries to direct cash assistance program in Alo’o and Ogolugus village in Ampibabo District in Parigi Moutong Regency. In addition, goal of this research is to acknowledge the implementation of fund utilization in direct cash assistance programs that have been distributed to the target households in those village. This methodology apply tabulation of frequency distribution technique. This study found that there are fourthy nine respondents claim that the program has positive impact on them. It means that the program can help the poor income level families. Also, the study found that this program had been implemented based on the government’s initiative. However, there are still many poor families have not have the positive impact of this program. In other words, there is an existing invalid data related to poor families so that other poor families could not obtain the benefit of the program.